Law Enforcement of Narcotics and Prohibited Drugs Among Youth that Impact on State Security and Sovereignty - Sri Mulyani Putri Jayanti; Yusuf Saefudin (Proceedings Series on Social Sciences & Humanities, 2023)
Cases of narcotics and drug abuse in Indonesia are increasingly worrying, this can be seen from the increasing number of narcotics use among the next generation of the nation, especially "teenagers". The rise of drug abuse cases among teenagers is certainly caused by several supporting factors, including high curiosity or trends and a friendship environment where someone considers new and challenging things to do, making children in adolescence easily fall into drug use. Drugs are dangerous substances that affect a person's psychiatric condition or psychology and cause addiction, which has the potential to become an obstacle to national development that threatens the security and sovereignty of the state. The problems faced are How is Law Enforcement Against Narcotics Crimes in Indonesia According to Law Number 35 of 2009 concerning Narcotics, and How is the Protection of Drug Abusing Children Viewed from the Aspects of Victimology. This writing examines secondary data in the form of secondary legal materials by understanding the law as a set of positive rules or norms in the legislative system that regulates human life (library research). Based on the results of the research, it is known that law enforcement against narcotics crimes according to the Narcotics Law is subject to imprisonment, fines, life imprisonment and other sanctions, protection for children who abuse drugs in terms of victimology aspects, namely rehabilitation because the child is on the one hand the perpetrator and the other side is the victim